(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Menopause is the term for the natural and permanent cessation of monthly female reproductive cycles. Menopausal women are known to experience physical, psychological, and vasomotor symptoms. In Ayurveda, menopause is not mentioned separately or as a disease but it is considered as Rajakshaya, the transition period of body from predominance of Pittadosha to Vatadosha. Rajonivritti (menopause) occurring in Jarapakva Shareer (aged body) at the age of 50 years. In modern science, hormone therapy has been used to control the symptoms of menopause. But long term use of this therapy had an increased risk for cardiovascular disease, stroke, breast cancer etc. A lifestyle modification is therefore an essential component in reducing menopausal symptoms, which includes a healthy diet, physical exercise, stress reduction and weight management. In this study 25 subjects with menopausal symptoms between the age group of 45 to 55 years were selected, from OPD of Govt. Ayurveda College Hospital, Tripunithura, as per the inclusion and exclusion criteria. The study subjects were advised to have two Yava saktu modakas of 10gm. each in morning at 7.30 a.m and the practice of Suryanamaskara and selected Pranayamas in the morning for 1 month. Assessment was done on 0th, 15th and 31st day of intervention. Along with this, the blood investigations like fasting blood sugar, post prandial blood sugar and serum cholesterol were assessed on 0th and 31st day of the study period. Results showed that Suryanamaskara, selected Pranayama and Yava saktu modaka have statistical significance in reducing menopausal symptoms.